Hybrid algorithms, techniques and implementations of fuzzy logic - Stanimirović, Ivan (Arcler Press, 2019)
Studies various aspects of Fuzzy logic including an extensive overview of hybrid algorithms, techniques and implementations. It includes definitions of evolutionary computation and fuzzy systems, ideologies and strategies. This book provides the reader with insights into the development of its knowledge, so as to understand the applications and implementations of fuzzy logic using hybrid algorithms.
Keywords: Fuzzy logic.; Fuzzy algorithms.; Logique floue.; Algorithmes flous.; Fuzzy algorithms; Fuzzy logic